Trade Liberalization and the Theory of Endogenous Protection: An Econometric Study of U.S. Import Policy - Trefler, Daniel (Journal of Political Economy, 1993)
Trade theorists continue to puzzle over their surprisingly small estimates of the impact of trade liberalization on imports. All explanations of the puzzle treat trade liberalization as a given. But the level of trade protection is not exogenous. The theory of endogenous protection predicts that higher levels of import penetration will lead to greater protection. This paper finds that when trade protection is modeled endogenously, its restrictive impact on imports is large, 10 times the size obtained from treating protection exogenously.